THE INFLUENCE OF INDIVIDUAL CHARACTERISTICS AND QUALITY OF WORK LIFE ON EMPLOYEE PERFORMANCE IN THE EMPLOYEE COOPERATIVE OF PASAR REBO HOSPITAL, EAST JAKARTA - Faradilah, Delia Nurul; Siswani, Sri; Nurminingsih; Ahmadun (Transpublika Publisher, 2023)
This quantitative study aimed to investigate and analyze the impact of individual characteristics (X1) and the quality of work life (X2) on employee performance within the Employee Cooperative at Pasar Rebo Hospital, located in East Jakarta. The research focused on three main aspects: (1) the influence of individual characteristics on employee performance, (2) the influence of the quality of work life on employee performance, and (3) the influence of individual characteristics on the quality of work life within the Employee Cooperative of Pasar Rebo Hospital. The study encompassed a total of 50 employees from the Pasar Rebo East Jakarta Hospital Employee Cooperative, employing a Total Sampling technique due to the limited population size (less than 100 employees). Data collection involved a combination of observation and questionnaire surveys. The findings revealed that there exists a non-significant relationship between individual characteristics (X1) and employee performance (Y), as indicated by a T-statistic of 0.621 (> 1.96). Despite the lack of statistical significance, the original sample estimate demonstrated a positive relationship between individual characteristics (X1) and employee performance (Y), with a value of 0.098. In contrast, the study revealed significant positive relationships between individual characteristics (X1) and the quality of work life (X2) (T-statistic = 4.813, < 1.96) and between the quality of work life (X2) and employee performance (Y) (T-statistic = 6.143, > 1.96). The original sample estimate values for both relationships were positive (0.471 and 0.570, respectively), highlighting the importance of fostering a positive quality of work life to enhance employee performance within the Employee Cooperative at Pasar Rebo Hospital.